The Effect of Motivation and Competence on Millennial Job Performance and Job Satisfaction - Charka, Rahma; AM, Trisniarty; Yamaly, Fadhil (International Journal of Business, Management and Economics, 2022)
Motivation and Competence are things that affect the good and bad performance of employees. Millennials thrive with immediate satisfaction from technology, spend a lot of time on social media, and are most commonly used to represent the lazy generation at work. This research aims to know the effect of motivation and competence on employee performance in the energy and mineral resources office of south Sumatra province. The object of research used in this study is Employee Performance (ɳ1) as an endogenous variable. The exogenous variables in this study are Motivation (ξ1) and Competence (ξ2). This research was conducted at the Department of Energy and Mineral Resources of South Sumatra Province. The research method used is associative research because the author wants to know the effect of Motivation and Competence, on performance. The population in this study was 102 people. Sampling techniques with purposive sampling so that the sample in this study is 82 employees. Research using SEM method with the help of Smart pls software. The results of this study show that either partially or together motivation and competence have a positive and significant effect on performance. Meanwhile, from the results of this study, there is no significant influence between job satisfaction as an intervening variable between motivation and competence on employee performance.